Empowering Women; basic right for being an Individual. - S. Faiza Batool; Ujala Sajid; Hira Qaisar (International Journal on Women Empowerment, 2022)
Background: Concept Women empowerment emerge from the middle of 20th century and now recognize globally. Empower the women from discrimination, inequality and injustice are the basic aspects of this approach. Gender equality, economic empowerment, social empowerment, political empowerment and education are all the integral of women empowerment which provide the safe space where they have rights for education, equal opportunities in social, economic and political status. Methodology: To investigate the gaps between the knowledge of empowering women and to found the real struggle of women on daily basis we applied both the quantitative and qualitative data collection procedure, which include the questionnaire with close-ended question and the interviews with selected women from different region. Results: Women with different background have different approaches and their empowerment vary according to it even though culture and social bounding’s hinder the pathway of empowerment. But it has been noted that the education and training sessions are helpful in bringing change in one’s narrative and behavior. Empowering the women; it’s not only the concept of girls education right, it also about their social, political and economic stability. Conclusion: Being human beings, women should also be treated as equals. With the growing world and interest of people in women's empowerment, it became the central aspect of each country's policies. We apply a mix-method research approach to address women's empowerment and the gaps in its knowledge, which include a questionnaire and interviews of the selected women. Hence our study suggests that training programs in different areas increase awareness and empowerment of women; however, societal and cultural barriers are the prominent hindrance associated with women's empowerment.